RANCANG BANGUN APLIKASI PELAYANAN PUBLIK BERBASIS WEB DILINGKUNGAN RW 03 RAWA BUAYA CENGKARENG JAKARTA BARAT - Fardillah Ramadhan; Munawaroh (Journal of Research and Publication Innovation, 2023)
Rukun Warga (RW) 03 is one of the areas in the Cengkareng swamp crocodile neighborhood, West Jakarta, the head of RW 03 is in charge of protecting the community in the RW 03 area and takes action when residents make reports or complaints. At present the reporting procedures in RW 03 are still running manually and have many shortcomings and weaknesses so that it has hampered the organizational performance of RW 03 and has not been able to support the needs desired by the existing community, starting from the process of inputting reports to managing reports that takes up enough time. This study aims to analyze and design a web-based reporting information system needed by the community of RW 03. Design a reporting information system using the Waterfall method as the system development and Unfied Modeling Language (UML) as the modeling tool. The function designed for this system consists of reporting violations in the RW 03 area as well as tracking reports that are input and management of existing reports. From this research that was carried out and it can be concluded that the website application for a public complaint service system can be a solution and improve the quality of services in the area. Of course, this complaint system has its drawbacks. Therefore, to improve the quality of system development, the authors suggest improving the design to make it attractive and developing applications so that they become mobile-based. Keywords: Design, Public Service, Black Box Testing, Unified Modeling Language (UML), Waterfall